Occurrence and pathology of naturally occurring biliary amphistomiasis in buffaloes and cattle - GHOSH, R C; CHAUHAN, H V S (The Indian Journal of Animal Sciences, 2013)
Studies Oil the occurrence and pathology of naturally occurring biliary amphistomiasis in buffaloes and cattle were conducted. The Occurrence of Gigantocotyle explanatun was much higher in buffaloes (87.09%) than in cattle (35%). Grossly, the liver was entarged and the cut surlace of the liver revealed numberous flukes in the humen of the bile-ducts. Histopathologically, there was marked proliferation of biledocts forming irregular acinous or tubular structures, arterioloselecrosis and lymphocylic infiltration in the interlobular connective tissue.